2011
DOI: 10.14238/pi51.5.2011.256-61
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of phototherapy with reflecting curtains on neonatal jaundice

Abstract: Background Although phototherapy has been used in clinical practice for 40 years, there is still much debate on how to provide the most efficacious phototherapy. Phototherapy with white reflecting curtains may increase the average spectral irradiance provided, as well as decrease serum bilirubin concentrations at a faster rate in neonates with jaundice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
(16 reference statements)
3
6
0
3
Order By: Relevance
“…9 Previous studies on phototherapy with reflectors in Kelantan (Malaysia) and Medan (Indonesia) used white reflecting curtains. 6,7 Results from both studies showed that white reflecting curtains increased the efficacy of phototherapy compared to phototherapy without reflectors. Both studies also showed that the phototherapy spectral irradiance with white reflecting curtains was 1.5-2 times greater than that of phototherapy without reflectors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Previous studies on phototherapy with reflectors in Kelantan (Malaysia) and Medan (Indonesia) used white reflecting curtains. 6,7 Results from both studies showed that white reflecting curtains increased the efficacy of phototherapy compared to phototherapy without reflectors. Both studies also showed that the phototherapy spectral irradiance with white reflecting curtains was 1.5-2 times greater than that of phototherapy without reflectors.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies also showed that the phototherapy spectral irradiance with white reflecting curtains was 1.5-2 times greater than that of phototherapy without reflectors. 6,7 By using aluminum foil as a reflector, about 92-98% of light is reflected, wavelength, and irradiance, and it resists corrosion. 10 Aluminum foil also is very thin and easy to fold into the desired shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian terdahulu di Kelantan, Malaysia, melaporkan hasil peningkatan intensitas terapi sinar 1,5 kali dan penelitian di Medan, Indonesia, sebesar 2 kali. 6,12 Penurunan kadar bilirubin serum total dan indirek lebih besar pada kelompok intervensi dibandingkan kelompok kontrol. Hal ini sesuai dengan penelitian terdahulu yang dilakukan di Malaysia, Medan, India dan Iran.…”
Section: Pembahasanunclassified
“…Terdapat modalitas dalam meningkatkan efektifitas terapi sinar yaitu dengan menambahkan material sebagai pemantul dan pemakaian terapi sinar ganda. [6][7][8][9][10][11][12] Penambahan material sebagai pemantul sangat bermanfaat terutama untuk negara yang sedang berkembang yang mempunyai keterbatasan biaya dalam pengadaan alat terapi sinar sehingga dapat memperpendek masa rawat serta menghemat biaya.…”
unclassified